Use of antibiotics for self-medication among university students in the health field: An integrative review (Research, Society and Development, 2024)
The present work aimed to carry out a bibliographical survey about self-medication with antibiotics among university students in the health field, highlighting the main causes and consequences, as well as understanding the factors that influence this practice. This is an integrative literature review study, in which articles were searched in the Pubmed, Virtual Health Library (VHL) and Science Direct databases, published between 2019 and 2023. For research the following descriptors were used: Self-medication; Antibiotic; Students. The terms were associated with the Boolean operator AND, written in Portuguese and English in the title and summary fields in both databases through advanced search. A total of 43 eligible publications were found, of which 15 were selected to compose this review according to the inclusion and exclusion criteria and the relationship with the proposed topic. Lack of knowledge on the subject, specifically, about the danger of inappropriate use of these medicines, low income in developing countries, facilitated access by health units, especially in community and retail pharmacies, incorrect purchase and administration are the primary factors behind the growth in the use of antibiotics for self-medication among university students.